Functional interaction between CFTR and Cx45 gap junction channels expressed in oocytes - Kotsias, Basilio Aristides (2005)
The cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride (Cl−) channel known to influence the function of other channels, including connexin channels. To further study potential functional interactions between CFTR and gap junction channels, we have co-expressed CFTR and connexin45 (Cx45) in Xenopus oocytes and monitored junctional conductance and voltage sensitivity by dual voltage clamp electrophysiology. In single oocytes expressing CFTR, an increase in cAMP caused by forskolin application induced a Cl− current and increased membrane conductance; application of diphenylamine carboxylic acid (CFTR blocker) readily blocked the Cl− current. With co-expression of CFTR and Cx45, application of forskolin to paired oocytes induced a typical outward current and increased junctional conductance (Gj). In addition, the presence of CFTR reduced the transjunctional voltage sensitivity of Cx45 channels without affecting the kinetics of junctional current inactivation. The drop in voltage sensitivity was further enhanced by forskolin application. The data indicate that CFTR influences cell-to-cell coupling mediated by Cx45 channels.